Pengaruh Work-Life Balance dan Komitmen Organisasi terhadap Turnover Intention: Peran Mediasi Stres Kerja pada Mahasiswa Magister Manajemen yang Bekerja - Raeesah Shalsabila Anjani Prameswary; Osly Usman (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to examine the effect of Work-Life Balance and Organizational Commitment on Turnover Intention with Job Stress as a mediating variable among working Master of Management students. This study applies the Job Demands-Resources Model and Social Exchange Theory to explain the relationships among variables. A quantitative approach with a causal research design was employed. The population consisted of 95 working Master of Management students enrolled in 2025, and 50 respondents were selected using purposive sampling. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that Work-Life Balance and Organizational Commitment have significant negative effects on Job Stress, while Job Stress has a significant positive effect on Turnover Intention. However, Work-Life Balance and Organizational Commitment do not directly affect Turnover Intention. Furthermore, Job Stress significantly mediates the effects of Work-Life Balance and Organizational Commitment on Turnover Intention. These findings indicate that reducing job stress is an important mechanism for lowering Turnover Intention among working students. The study contributes to the application of the Job Demands-Resources Model and Social Exchange Theory in the context of working graduate students.